Model Sistem Pendukung Keputusan untuk Penentuan Dosen Pembimbing Skripsi dengan Metode Profile Matching - Adri Maulana Zahari; Liza Efriyanti; Supratman Zakir; Riri Okra (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
Thesis supervisors play an important role in maintaining academic quality and supporting students’ timely completion of their studies. However, at the Faculty of Tarbiyah and Teacher Training, UIN Sjech M. Djamil Djambek Bukittinggi, the assignment of thesis supervisors is still conducted manually, potentially causing procedural inefficiency, unequal supervision workloads, and limited access for students. This study aimed to develop a decision support system for thesis supervisor assignment using the Profile Matching method to align lecturers’ competencies with students’ thesis topics. The study employed a Research and Development (R&D) approach using the Waterfall model, which included needs analysis, system design, implementation, and testing. The result of this study is a decision support system that assists the Head of Study Program in assigning supervisors more objectively, evenly, and efficiently, while also facilitating electronic thesis title submission. The system was developed with reference to the ISO 25010 software quality standard to ensure its functionality and reliability. This study contributes to the development of decision support systems in higher education academic services through the application of Profile Matching for a more objective and structured thesis supervisor assignment process. Abstrak Dosen Pembimbing Skripsi (DPS) berperan penting dalam menjaga mutu akademik dan mendukung penyelesaian studi mahasiswa secara tepat waktu. Namun, di Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sjech M. Djamil Djambek Bukittinggi, penentuan DPS masih dilakukan secara manual, sehingga berpotensi menimbulkan inefisiensi, ketidakmerataan beban bimbingan, dan hambatan akses bagi mahasiswa. Penelitian ini bertujuan mengembangkan sistem pendukung keputusan penentuan DPS menggunakan metode Profile Matching agar rekomendasi dosen pembimbing sesuai dengan kompetensi dosen dan topik skripsi mahasiswa. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model pengembangan Waterfall yang meliputi analisis kebutuhan, perancangan, implementasi, dan pengujian sistem. Hasil penelitian berupa sistem pendukung keputusan yang membantu Ketua Program Studi menetapkan dosen pembimbing secara lebih objektif, merata, dan efisien, sekaligus memfasilitasi pengajuan judul skripsi secara elektronik. Sistem dikembangkan mengacu pada standar kualitas perangkat lunak ISO 25010 untuk memastikan aspek fungsionalitas dan keandalannya. Penelitian ini berkontribusi pada pengembangan sistem pendukung keputusan dalam layanan akademik perguruan tinggi melalui penerapan Profile Matching untuk penentuan dosen pembimbing skripsi yang lebih objektif dan terstruktur.